Comparing the Injury Profile, Service Use, Outcomes, and Comorbidities of People With Severe TBI Across Urban, Regional, and Remote Populations in New South Wales: A Multicentre Study. Issue 2 (March 2016) - Simpson, Grahame K.; Daher, Maysaa; Hodgkinson, Adeline; Strettles, Barbara
Abstract : Objective: To compare the demographic/injury profile, outcomes, service utilization, and unmet service needs of individuals with severe traumatic brain injury across urban, regional, and remote areas of New South Wales. Setting: The 11 community-based rehabilitation teams of the New South Wales Brain Injury Rehabilitation Program. Participants: Active clients ( N = 503) with severe traumatic brain injury. Design: A prospective cross-sectional multicenter study. Main Measures: Overt Behaviour Scale, Health of the Nation Outcome Scale-Acquired Brain Injury, Disability Rating Scale, Sydney Psychosocial Reintegration Scale-2, Care and Needs Scale, data protocol on service utilization, and unmet needs. Results: There were no differences in injury severity or functional outcomes across the 3 locations. However, clients in regional and remote areas had significantly higher levels of premorbid and postinjury comorbidities and lower levels of participation in comparison to urban clients. Although accessing the same number of services as their urban counterparts, clients in regional and remote areas had significantly higher levels of unmet needs suggesting problems with under-servicing. Conclusions: Geographical location had a significant impact on service access and outcomes.